THE IMPLEMENTATION OF MIND MAPPING IN TEACHING WRITING NARRATIVE TEXT FOT TENTH GRADES OF SMAN 18 SURABAYA (RETAIN, 2013)
Abstract Writing is one of the language skills that has to be mastered by the students as well as the three other skills. Writing is considered the most difficult one because when doing writing activity, the students are required to pay attention to the content, organization, vocabulary, language use and mechanics simultaneously. The students also should arrange and organize the ideas clearly so that the readers do not misunderstand on what they write. The students also sometimes get difficulties in getting ideas to write. Because of many things that the students have to think to make a good writing, the students often get difficulties in expressing their ideas into a well composition. The mind mapping is effective strategy that can help the students in creating well composition because they are allowed to discuss their composition with their partners. Mind mapping also allowed the students to get and improves by observing the story given by teacher. For the reason, the researcher is interested to exploring the implementation of writing narrative texts by using mind mapping to the tenth graders and find out how are the students’ compositions after using mind mapping method. Writing activity needs long process that consists of pre – writing, drafting, revising, editing and publishing. The implementation of writing narrative texts by using mind mapping follows the steps of the writing process. Think pair share technique itself has three stages that are think , pair and share. So, in the implementation, the students do revising and editing activities in the “think” stage. While, the students do revising and editing activities in the “pair” stage. At the last, they can publish their composition in “share” stage. One of text types that can be taught by using mind mapping is narrative text. It is one of the texts which is taught to tenth graders of Senior High School. The researcher used descriptive qualitative researcher in conducting her study. The subjects of the study were the teacher and tenth graders of SMAN 18 Surabaya. The class observed was X – 5. The researcher instruments that were used by the researcher to collect the data were observation checklist, observation field note, and the students’ task. Those instruments were used to describe the way how the teacher implemented the mind mappingin teaching narrative texts and the students’ writing composition. From the data that was collected during observations, is revealed that the implementation of mind mapping was conducted twice in three meeting. The implementation was successfully and also can help the students to improve their writing skills. Is proven from the students’ writing progress in terms of each component in composition. The researcher concluded that the implementation mind mapping was effective to be used in teaching narrative texts; especially to the tenth graders of SMAN 18 Surabaya because the implementation of the technique and method could run well and could help the students create well composition. Moreover, the researcher expects for further researcher to conduct a similar research about the implementation of mind mapping in different skills. Key words : teaching writing, narrative text, the mind mapping. INTRODUCTION English is an important language spoken in international affairs and is used as the medium of information flow on science, technology, and culture as well. Since we are in a developing country, considerable efforts should be put forth to communicate in English favorably to make firm relationships with other countries so that we can apprehend the mastery of the science, technology and culture in the world, by which we can deal properly with the more and more demanding competition in the global era. By mastering English, we are one step closer in building a beneficial relationship with other countries worldwide more than ever. “Within the context of education, English language serves as a means to communicate in order to meet everyday communication, acquiring knowledge, a tool to foster interpersonal relationships, exchanging information, and savoring the aesthetics of language in English culture (Depdikbud, 2003: 6). In accordance to this statement, the language skills required to be achieved are divided into two parts of language functions, namely, oral and written English as a means of communication. In this case, listening and speaking are oral language; reading and writing are written language (Allwright, 1991:84). In this research, a deep concern comes to the researcher to analyze an approach to the writing skill of the High School students. Writing skill is very fundamental in every aspect of life, primarily for the purpose of studying English. It is such an irony that teaching writing still lacks of adequate emphasis both from the teacher and the students. Generally there are many types of writing that can be used such as narrative, descriptive, explanation, recount, information, report, exposition, and argumentation. (Meyers, 2005:17). Often, the conventional teaching writing process revolves around the generalization of writing ability only. The teacher only explains what and how the application of the four skills of writing is, without further explanation about using specific techniques that can help students to be more stimulated in choosing their words or forming the correct structure of their writing. It is essential to understand how far the importance of writing skill. Hence, the researcher conducted primary observation in one proposed high school, it is SMAN 18 Surabaya. Through the observation, the researcher intends to know to what extent the students comprehend the text. The researcher tries to focus on narrative text in particular, because the text belongs to the basic competence of senior high curriculum. In this observation, the researcher views that the skill of writing narrative text especially for X5 students is low. It is proved from the students’ passive manners in responding every question from the teacher and from their works as well. After making deeper observation the researcher begins to understand this situation, it is because the teacher teaches in a common way. The teacher only gave students a narrative text before she asked them to look up for any difficult vocabularies and then the students are instructed to do the exercises related with the text. Afterwards, the teacher ordered the students to rewrite the narrative text at home, overseeing the urgency of providing further explanation regarding the text. This is worsened by the students’ passive manner to ask question, therefore it is quite hard for them to understand the text. Whereas, in teaching and learning process of writing, the teacher holds an important role. John (1997: 12) states that, “Teacher’s role is to help students develop viable strategies for getting started (finding topics, generating ideas and information, focusing and planning, structure and procedure), for drafting (encouraging multiple drafts of reading), for revising (adding, deleting, modifying and rearranging ideas), and for editing (attending to vocabulary, sentence, structure, grammar, and mechanics)” From the existed background, the researcher attempts to offer a method to overcome the problem by using mind mapping method in teaching narrative text. The Researcher chooses mind mapping because mind mapping offers structured and practical method of guiding students throughout the writing steps. Mind mapping will be helpful because from the first observation, the researcher realizes that the students’ weaknesses are in the difficulties in comprehending and developing sentences in a passage. Mind mapping approach is used to generate, visualize, structure, and classify ideas, and as an aid to studying and organizing information, solving problems, making decisions, and writing. It is hoped that by applying this long well-known method, the students will be able to produce a writing piece more naturally and efficiently to achieve desired results and standards. Based on the research, the statement of the problems are: 1) How is the implementation of mind mapping in improving students writing, 2) How the students’ composition after using mind mapping. METHODOLOGY Based on the research questions and the objectives of the study in the previous chapter , the researcher will use a descriptive qualitative to gather information that are related to the improving writing narrative text by using mind mapping for the tenth grade students of SMAN 18 Surabaya. Ary et al ( 2010:419) states that qualitative research is a research that investigates the quality of relationships, activities, situation and materials. Ary at el ( 2010;424) also states that qualitative research studies behavior as it occurs naturally in a classroom. It means that the researcher only observes the teaching and learning process without taking part in the process. On the other hand, Huda (1999:37-38) states that the definition of qualitative research is frequently associated with the technique of analyzing data and writing research report. Research report for qualitative research is descriptive. Based on the statement of both experts, it means that qualitative research allows the researcher to observe the situation that happens naturally and then describes it in the form of words and sentences to represent the data. In this study, the researcher will describes the teaching and learning process in the class and also describe the students’ composition as the result of the teaching and learning process. This study is held at SMAN 18 Surabaya. The subjects of the study are the teacher and the tenth grade students of SMAN 18 Surabaya. The researcher chooses X-6 class as a class that will be observed. The class consists of 33 students 23 male and 10 female. In this study, the data of the study deal with the result of the observation and the result of students’ tasks. The result of observation covers the teacher’s activities during the teaching and learning process. The teacher’s activities are about the way how the teacher implements writing narrative text by using mind mapping. While, the result of students’ task is the narrative composition that the students writing. The components (Content, Organization, Vocabulary, Language use and Mechanics) of the composition will be analyzed to find the result. All of the data which take from the observation checklist and field notes and students’ task are analyzed qualitatively in a descriptive way in the form of words and sentences. The data are obtained from the teaching and learning process in the classroom. The data are analyzed based on result of observation and the students’ task. After filling the observation checklist and field notes for each meeting, the researcher will analyze the activities done by the teacher dealing with improving writing narrative text using mind mapping. The results of observation describe the teaching and learning process when the combination of writing narrative text and mind mapping are implemented in the classroom. While, the students’ task are collected are used to analyze the students’ narrative composition in the terms of organization, content, vocabulary, language use and mechanic. The result of analyzing the students’ narrative composition describe the students’ writing ability in narrative texts. Form the analysis, the students’ writing ability in what component of composition that increased can be known. In analyzing the students’ composition, the researcher used the rubric of ESL composition profile by Jacob et al ( 1981 ;90 ) RESULT AND DISCUSSION 4.1 The Implementation Of Writing Narrative Text By Using Mind Mapping 4.1.1 The Result of The Implementation of The Writing Narrative Text Using Mind Mapping In this section, the researcher describes the observation result of the implementation of using mind mapping in teaching narrative texts. The researcher did not apply the implementation of writing narrative text by using mind mapping by herself but the teacher did. The researcher just observed all activities in the classroom during the teaching and learning process. The researcher did observation in three meetings. In the first meeting, the teacher only explained about narrative text and provided example using mind mapping. In this research, fairy tales is chosen to implemented narrative texts using mind mapping. The first implementation of writing narrative text using mind mapping was done in the second mapping, while the second implementation of writing narrative text using mind mapping was done in the third meeting. 4.1.1.1 The First Implementation (second meeting) The second meeting was held on 15th February 2013. There would be presentation. The time was 2x 40 minutes. Before the teaching and learning process started, the teacher greeted them and checked their attendance by calling their names one by one. The teacher then reviewed the lesson in the previous meeting. And the teacher ask the students to make a pairAfter the students had taken seat with their pair, the teacher gave the story entitled ‘Snow White’ to the students to retell with they own words. The students were very happy because they like that story. The teacher then read the story, the pairs were allowed to prepare to write the story. The teacher then asked the students to think about what they were going to write, they were allowed to collect ideas and configured in mind mapping to help their works. Here is the dialogue between the teacher and the students. Teacher : Ok, you have taken seat with your pair and I have prepared the story. Now you can start to think about what you are going to write based on the story that I have read for you. You can start to make mind mapping first. Student 4 : Bu, ini setelah dibuat mind mapping trus kita nulis pake bahasa sendiri ya? Teacher : Yes that’s right. Student 5 : Bu, nulisnya on the paper or on the book? Teacher :On a piece of paper. Nulisnya di kertas saja ya anak – anak biar ibu tidak terlalu berat bawa buku kalian. Students :Iya bu. The teacher allowed the students to open dictionary if they figured out difficulties in translation. She had prepared some dictionaries on her table and the students might borrow them if they don’t bring any. However, some students had brought dictionaries by themselves. When the students were doing their task, the teacher walked around the class to monitor their work. The teacher allocated 25 minutes in the ‘thinking’ stage. After the time was up, the teacher asked the students to discuss their composition with their pair. When the students started discussing, the class became lively. They looked enthusiastic in discussion. Most of the students were discussing, the teacher did not just sit on her chair but she walked around the class to supervise on the students’ discussion. Most of the students revised and edited their composition after getting feedback from their pair but some of the students had been self – confident with their work. When the time was up, the teacher asked the students to submit their composition to her. She then told that she would ask some students to write down the mind mapping on the white board and read the story in front of class. She allocated 20 minutes. The first chance was given to Fransiska to write her mind mapping on the white board and read the story. The teacher told the students that she would give participation score for those who gave comments or suggestions to Fransiska composition. The score made the students enthusiastic in giving comments. Many students participated in giving evaluation to Fransiska’s composition but the teacher only chose some of them. They were Norma, Oktaviani and Fara, here is dialogue between the teacher and the students. Teacher : Ok, Fransiska, please come forward. Fransiska : Oh, no bu, yang lain dulu aja lo bu.. Teacher : Gak, kamu dulu, ayo. Fransiska : Gak mau bu, malu banyak yang salah nanti Teacher ; It’s ok, nanti kita benarkan bersama – sama Fransiska : Ok deh bu.. ( Fransiska came forward and start writing her mind mapping on the whiteboard) Teacher : While Fransiska is writing her mind mapping, you should observe and find errors of the composition. I will give you participant score if you give comment and suggestion to fransiska’s composition. Students ; Yes ma’am.. The discussion of Fransiska’s composition in the share stage ran well. The teacher could lead the discussion well. After the teacher had corrected Fransiska’s composition, she asked other students to share their compositions in front of the class consecutively. The teacher gave the chance to Andini to share her composition. The discussion atmosphere of Andini‘s composition was similar to the discussion atmosphere of fransiska’s. the students were enthusiastic in giving comment or suggestion. 4.1.1.2 The Second implementation (Third Meeting ) The third meeting was done on February 22th , 2013. There were 24 students who were present. The time was 2x 45 minutes. As usual, the teacher greeted the students and checked their attendance by fostering their names one by one. The teacher also reviewed the lesson in the previous meeting. After reviewing the lesson, the teacher asked students’ opinion toward the technique and media that were used in the previous meeting. She then asked the students to make a narrative text based on the stories given. Here is the dialogue between the teacher and the students. Teacher : Ok, in the previous meeting, you have got a writing task by using mind mapping do you enjoy it? Students : yes maam.. Teacher : Why do you like it? Student2 : Because memudahkan ma’am, walaupun bentuknya agak aneh gitu. Student4 : Kalo saya suka soalnya jadi lebih cepet ngerjain mam, gak lama kalau mau nulis narrative text ma’am… Teacher : You’re right. Mind mapping can make us easier in writing a composition. Nah kalau minggu lalu kalian sudah berpasanganm sekarang kita akan melakukan individual ya. And I have Cinderella storie, I want you to make another narrative text now. Student5 : Apa?nulis lagi mam? Student6 :Tenang.. ini tugas menulis narrative text yang terakhir ya. Ibu sudah meyiapkan cerita Cinderella untuk kalian tulis lagi secara narrative text menggunakan… Students : Mind mapping ma’am…. The students then started observing the stories and thinking about what they were going to write. They also started writing narrative text based on the story given. When they were writing, the teacher walked around the class to see their work. She allowed the students to open dictionaries if they got difficulties in translation. The teacher only gave 45 minutes for the students to make some important points for their mind mapping and elaborate it as a complete stories with their own words. When the time was up, she asked to the students to stop writing and start the discussion. When the students were discussing, the class became closely. They looked enthusiastic in giving comments to their friends. The discussion was monitored by the teacher by circulating around the class during the students’ discussion, the teacher motivated them to use English in this stage. In this section, she allowed the students to revise and edit their composition based on the feedback from their friend. She allocated 20 minutes for discussion. When the time to discuss was up, the teacher then asked the students to collect their composition to her. Then, they would commence the ‘sharing’ stage. In this stage she invited two students to share their compositions in front of their friends. They were Fara dina and Oktaviani Teacher : Ok, you have done think stage. Now, you have share stage. I want faraDina to come forward.. Diana :Lho bu, kok saya bu? Punya saya banyak yang salah bu, malu… Teacher : Gak apa- apa salah nanti kan dbetulkan. ( Fara comes forward and writes down her composition on the whiteboard ) Teacher : Ok, while Fara is writing her composition, you all have to observe it and find the errors of fara’s composition so that you can give comment Student10 : Dapat nilai tambahan kan bu kalau kasih komentar? Teacher : Iya, pasti… ( a few minutes later, Fara finished writing her composition. ) Teacher : Ok, Fara has finished writing her composition. Now, the time for you to give comments or suggestions. Some students : ( raising their hands ) Teacher : Ya, Titan. Titan : Komentar saya, farah story is good enough,. Pengembangan ceritanya bagus. Pemilihan vocabullarynya juga bagus namun sedikit kurang pada grammarnya, itu aja sih maam. Teacher : Ok, that’s a good comments. Anyone else? Septian : (Raise hand ) saya maam, ceritanya complit maam dari awal sampe akhir. Penjelasannya detail dan kata – katanya bagus maam. Teacher : Ok, we have two comments for Sarah story. Now, we will discuss the stories together. I think all over it’s a good writing, Good job Farah. Memang masih ada kekurangannya dalam hal grammarnya, namun karena disini kita membahas pengembangan cerita, jadi Fara’s writing is a good one. Give applause for Fara guys ( All of students are clapping their hands ) Teacher : Now, we will discuss the second writing. The second writing’s comes from Oktaviani ( oktaviani come forward and start to write her story in a white board ) ( fiew minutes later ) Teacher : So, who will be the next commentator? Mahadika : ( raise hand ) me maam ! Teacher : Yes, please. Mahardika; Dari segi cerita memang sudah terlihat pengembangannya lumayan bagus maam, Tapi mungkin grammar dan vocabulllarynya yang membuat tulisan okta terbaca sedikit kacau maam. Jadi mungkin bias lebih diperbaiki dari sisi tersebut, sehingga ceritanya lebih jelas. Teacher : Well, memang kalau ibu baca kelemahan karangan okta ini adalah bersumber dari structure dan vocabullarynya. So, untuk Okta. You have to organize the story by using an appropriate baik dari segi ejaan dan pemilihannya. Because the time is limited, the teacher just gave opportunities to the students to give a comment. After the discussion of Diana’s composition finished, the teacher asked other student to share their composition. The student who got the chance to share the composition was Zaky. The discussion of his composition was running well. The atmosphere of the discussion seemed alive because his friends were enthusiastic in giving comments to his composition. The students’ comments were about the mechanics and language use. Time to share was up. Then the teacher asked the students’ difficulties is writing narrative text and gave feedback on students’ composition. She also asked to her students to practice making narrative text at home. She then said good bye before leaving the classroom. 4.1.2 The Discussion of The Implementation Mind Mapping To Improve Writing Narrative Text The researcher did the observation in three times. They were 7th, 15th and 22nd February 2013, after the researcher finished observing the implementation of mind mapping to improve writing Narrative text, she found that mind mapping could be implemented in teaching narrative text. When the mind mapping and writing narrative text was implemented, the students could do well in every stage of TPS technique because they could understand the teacher’s instructions. The teacher allocated 25 minutes in the think stage. From the result of observations on the implementation of think stage that were done twice, it can be stated that the students looked enthusiastic because they could collect ideas by observing the story given. But, in the first implementation, there were some students who still got difficulties in developing their ideas into paragraph. While, in the second implementation most of the students did not get difficulties anymore in developing their ideas into paragraph because they had known how to make narrative text well. In this stage, the teacher allowed the students to use dictionaries if they got difficulties in translating vocabulary from Indonesia to English. Most of them could finish their composition on time. The implementation of mind mapping had proved that it could help the students to create narrative texts easier as discussed in the earlier chapters. The teacher gave 20 minutes for the students to discuss their compositions with their pairs. The students could exchange feedback of their composition. They were enthusiastic in asking and giving comments for their pairs. They were also allowed to revise and edit their composition in this part. The teacher allocated 20 minutes for the students to share their composition in front of the class. Both implementations of share stage and the discussion could run well. This part gave a chance for the students to get comments or suggestions from their composition in front of the class. When the students were sharing their composition, the atmosphere in the class seemed alive because many students were interested in giving comments or suggestions to their friend’s composition. From the discussion above, it can be stated that the implementation of writing narrative text using mind mapping was effective to teach writing narrative texts. In the beginning, it’s allowed the students to think about what they are going to write by observing the stories had been prepared by the teacher. At, the same time, the students were also allowed to start writing narrative text individually. Then, after writing their composition they allowed to discuss their composition with their pairs so that the students could revise and edit their composition to be a better one before they submitted them to the teacher. While next are gave a chance for the students to get comments or suggestions from their friends and teacher by sharing their compositions in front of the class so that they would be able to write better composition later. 4.2 The Writing Ability Of The Implementation Writing narrative Text Using Mind Mapping 4.2.1 The Result of Students’ Writing Narrative Texts By Using Mind Mapping In this section, the researcher will describe the result from students’ task. The result of the students’ tasks was used to recognize the students’ writing ability of narrative texts. The researcher collected the students’ tasks from the implementation of writing narrative text using mind mapping. The researcher evaluated the students’ narrative composition based on ESL composition Profile Taken from Jacob et al. (1981), before the researcher classified the students’ composition into five components which should be evaluated. They are content, organization, vocabulary, language, use, and mechanics. Each component was categorized into four levels. Those are excellent to very good, good, good to average, fair to poor and very poor. 4.2.1.1 The Content of students’ Writing Composition In a composition, content is an important component because it conveys the writer’s idea. Based on ESL Composition profile by Jacob et al (1981), there are four criteria in evaluating content. They are knowledgeable, substantive, through development of thesis and relevant to assign the topic. Content was categorized in four levels, they are excellent to very good, good to average, fair to poor, and very poor. The students’ composition in terms of content showed good result. In the first implementation of writing narrative text using mind mapping, there were no students who were in very poor level and there were several students who were in fair to poor level. While in the second implementation, there were no students who were in very poor level and there were only few students who were in fair to poor level. It means that there was improvement in students’ composition in terms of content. In this session, the researcher will discuss the student’s composition that got improved in terms of content. The figures below are from the students’ composition that got improved in terms of content from “ good to average” to “ excellent to very good” level. Figure 1. The student’s final composition in the first implementation Name : Andita ( 16 ) Snow White A long time ago live a king and queen, they’re have a child. The name Snow white. The queen was dead and then the king married again. The step queen really weak. Snow white was treated like servent. Snow white ridding horse and go so far in palace. And than live a witch. She has a magic mirror. The witch ask “ who’s Fairest in the world ?” and then the magic mirror says snow white fairest in the world. The witch was very angry and told huntersman to kill snow white. But, the huntersman was really kind person, and told snow white to went so far away. Snow white riding horse until in the jungle. And then, she found a little house. The little house’s seven little dwarfs. Snow white was really tired and soon sleep. Seven little dwarfs shock looked a snow white. Day by day, snow white live with seven little dwarfs . at this moment, the witch came in a little house and give apple to snow white. The apple is poisonous, but snow white not know about it. And then snow white ate a apple. Not long time, snow white was dead. The king riding horse in the jungle and found a snow white in a glass coffin. And the king kiss her, Snow White was get up with smile. The end story they were married and live so happy ever forever. In terms of content, the composition the figure I showed that the students not clearly understood the content or plot of the story .This is mostly evident first and second paragraph, in which the student misrepresents the generic characterization of the folklore. Despite those major drifts from the content, the composition finds its way back to the actual plot and characterization in the third and fourth paragraph. The composition was mostly relevant to the topic, but it was lack of detail. Hence, the composition was assigned in ‘good to average’ level. Figure 2. The student’s final composition in the second implementation Anindita ( 16 ) Cinderella Once upon a time, live happily family. They’re father’s Cinderella, mother’s Cinderella and Cinderella. Then her mother was die, and her father married again. Her father went to the town for a long time, but her father was dead because had a problem. Cinderella was sad and cry, she lived with step mother and two step sisters. Cinderella was busy because she was like a servant. In the palace, the prince wanted to married and looking for a wife, He invited people in the kingdom to came to the party. But, Cinderella didn’t come in that party because her step mother didn’t allow her to come to the party. Cinderella was sad. At the time, fairy mother came and helped Cinderella like a princess, she was really beautiful, but she must come back before a midnight from the party. At the party, Cinderella dance with prince. Prince falling in love with Cinderella. Unfortunately, the midnight was came, Cinderella run away and her drop glasses shoe. One day, the prince looked for who Has a drop glasses shoe yesterday. He told someman to looked who drop glasses. All women in the kingdom was tried to wear glasses shoe and then, Cinderella was tried to use it. The prince was shocked and happily. Finally, Cinderella married with the prince and they’re happily ever after. While, the composition in the figure 2 showed It is show that the student’s ability in writing narrative text in terms of content improved significantly. The students’ composition reflected knowledgeably on the content of story. The student also could create good composition that was relevant to assign the topic. This composition allows a devoted storytelling as it was meant to be, but with the student’ own words and style. So, it can be included in excellent to very good level in terms of content. 4.2.2 The Discussion of Students’ Writing narrative texts after the implementation writing narrative text using mind mapping. The researcher used ESL Composition Profile by Jacob et al to analyze the students’ composition. There were five components of composition that were analyzed. They are content, organization, vocabulary, language use and mechanics. Each component of the composition was categorized in four levels that are excellent to very good, good to average, fair to poor and very poor. The teacher implemented writing narrative text using mind mapping twice in three meetings that were in the second meeting and in the third meeting. In each implementation, the teacher gave a task to the students to write a narrative text by using mind mapping. The result of students’ task showed that there was improvement of the students’ ability in writing narrative texts. There was progress on the students’ ability in writing narrative texts in the second implementation of writing narrative text using mind mapping. The result of student’ task revealed that the students’ ability in writing narrative composition in terms of content got improved. Most of the students were able to deliver knowledge of object that they described in the second implementation. In the first implementation, there were 12 students who were in fair to poor level. 10 students got good to average. While, in the second implementation, there were 3 students got fair to poor level. 14 students got good to average level and 5 students got excellent to very good level. In terms of organization, the result of students’ task revealed that the students’ ability in writing narrative text improved. At the first implementation, some students still got difficulties in organizing their paragraph. But, in the second one, they had understood more about the generic structure of narrative texts so that they could express their ideas into well – organized composition. In the first implementation, there were 2 students who got fair to poor. 12 students got good to average level and 8 students who got excellent to very poor level. While, in the second implementation, there were 12 students who got good to average level and 10 students got excellent to very good. The result of students’ task revealed that the students’ ability in writing narrative composition in terms of vocabulary got improved. Most of the students had been able to use the appropriate words and the meaning was not obscured. In the first implementation, there were 6 students who got fair to poor level and 16 students got good to average level. While, in the second implementation, there were 12 students who got good to average and 10 students got excellent to very good. In terms of language use, the result of students’ task revealed that the students’ abil.oty in writing narrative composition improved significantly. At the first implementation, the students still got difficulties in constructing sentences in simple present tense correctly. But, in the second day of implementation, the students were able to overcome their difficulties. In the first implementation there were 2 students who got very poor. 5 students got fair to poor and 15 students got good to average. While, in the second implementation, there were 15 students who got good to average and 7 students got excellent to very good. The result of the students’ task revealed that the students’ ability in writing composition in terms of mechanics improved greatly. In the first implementation, many of the students did not pay attention to the punctuation, capitalization and spelling on their compositions. But in the second implementation, many students did not repeat their errors. In the first implementation, there were 4 students who got very poor, 12 students got fair to poor and 6 students got good to average. While, in the second implementation, there were 6 students who were in fair to poor level. 6 students were in good to average level and 10 students were in excellent to very good level. CONCLUSION AND SUGGESTION Conclusion After the researcher conducted the research and the result, the researcher make conclusion related to the research question which are stated in chapter one. Based on the result of observation, it can be concluded that : The implementation of writing narrative text by using mind mapping to tenth grades students’. The data from the observation checklist and field notes revealed that the implementation of mind mapping to teach narrative texts could run successfully. The students could follow the activity in each stage of the mind mapping well. In first stage, the students collected their by observing the story given by the teacher and then started writing narrative text based on the story that they observed, in the second stage, the students discussed their composition with their pair. The students also revised and edited their composition based on the feedback from their pairs. In the last stage, the students shared their opinion or their knowledge by giving comments or suggestions to their friends’ composition written in front of the class. hemind mapping can help the students create better composition. It could be proved from the progress of students’ ability in writing narrative texts. In the second implementation of writing narrative text, it can be known that the students’ composition was better because the students had chances to share their knowledge of narrative texts with their friends in pair stage and share stage of the first implementation of mind mapping. Suggestion In this section, the researcher would like to give some suggestion that are dedicated for the teacher and other researchers. For the teacher The teacher can apply the combination of mind mapping and writing narrative texts not only for teaching writing narrative texts but also for teaching writing any kinds of text, such as descriptive texts, procedure texts, etc. the teacher can also apply the writing narrative texts using mind mapping not only for tenth grades students but also for all kinds of level, such as for the eleventh grade students and twelve grade students. For other researcher It is suggestion that further researcher conducts a similar research about the implementation of the writing narrative texts using mind mapping in different skills. The researcher also hopes that the further researcher conducts the experimental study in order to improve some findings in the study of the writing narrative text using mind mapping because this study was narrative qualitative. REFERENCES Alice, Oshima, dkk. 1991. Writing Academic English. New York: Longman. Allwright, Dick. 1991. Focus in the Language Classroom. Cambridge: Cambridge University Press. Anderson, Mark. 1997. Text Type in English 2. Australia: Mackmillan. Boardman, Cynthia. A. 2002. Writing to Communicate (Paragraph and Essay). New York: Longman. Bram, Barli. 1995. Write Well, Improving Writing Skill. Yogyakarta: Kanisius. Departemen Pendidikan dan Kebudayaan. 2005. CBC Students Work Book Grade XIA. Semarang. Elliot, J. 1998. Action Research For Education Change. Philedelphia: Open University Press. Gribs, William. 2002. Teaching and Researching Writing. London: Longman.. Harmer, Jeremy. 2004. How to Teach Writing. New York: Longman. Hogue, Ann. 1996. First Step in Academic Writing. New York: Longman. Hyland, Ken. 2004. Genre and Second Language Writing: London: The University of Michigan Press. Hyland, Ken. 2004. Teaching and Researching Writing. London: The University of Michigan Press.